Sensors and Microsystems Proceedings of the 19th AISEM 2017 National Conference (Lecture Notes in Electrical Engineering,, 2018)
This book showcases the state of the art in the field of sensors and microsystems, revealing the impressive potential of novel methodologies and technologies. It covers a broad range of aspects, including: bio-, physical and chemical sensors; actuators; micro- and nano-structured materials; mechanisms of interaction and signal transduction; polymers and biomaterials; sensor electronics and instrumentation; analytical microsystems, recognition systems and signal analysis; and sensor networks, as well as manufacturing technologies, environmental, food and biomedical applications. The book gathers a selection of papers presented at the 19th AISEM National Conference on Sensors and Microsystems. Held in Lecce, Italy in February 2017, the event brought together researchers, end users, technology teams and policy makers. .